2020
DOI: 10.1136/bmjdrc-2019-000972
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of early to mid-life adulthood BMI and incident diabetes: the China Health and Nutrition Survey

Abstract: IntroductionThis longitudinal study aims to characterize distinct body mass index (BMI) trajectories during early to mid-life adulthood and to explore the association between BMI change from young adulthood to midlife and incident diabetes.Research design and methodsThis study included 7289 adults who had repeatedly measured BMI 3–9 times during 1989–2011 and information on incident diabetes. Latent class growth mixed model (LCGMM) was used to identify different BMI trajectories. Cox proportional hazard models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 32 publications
(25 reference statements)
7
38
0
Order By: Relevance
“…The low-increasing group, with baseline BMI around 20 kg/m 2 , increased slowly during the 20–60 years period, while the high-increasing group with lower baseline BMI increased rapidly. Some studies, using data from China, the UK and Finland, explored BMI trajectories for childhood and early adulthood, showed that BMI may have 2–6 trajectories 13 14 20–25. Though the numbers of trajectories were different among these studies, they all discovered a low-increasing or low-stable group and a high-increasing group, 13 1420–25 which was in line with our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The low-increasing group, with baseline BMI around 20 kg/m 2 , increased slowly during the 20–60 years period, while the high-increasing group with lower baseline BMI increased rapidly. Some studies, using data from China, the UK and Finland, explored BMI trajectories for childhood and early adulthood, showed that BMI may have 2–6 trajectories 13 14 20–25. Though the numbers of trajectories were different among these studies, they all discovered a low-increasing or low-stable group and a high-increasing group, 13 1420–25 which was in line with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Logistic regression models were used to examine the associations of model-estimated levels and linear slopes of BMI and WC at each age point with incident hypertension. Before logistic regression analyses, the model-estimated linear slope values of BMI and WC at each age point were adjusted for their corresponding levels to avoid collinearity of levels and linear slopes in the same model 20 21. Standardised ORs of levels and level-adjusted slopes of BMI and WC for incident hypertension were estimated, adjusted for gender, baseline SBP, smoking and alcohol drinking.…”
Section: Introductionmentioning
confidence: 99%
“…A sharp increase in weight has been associated with an increase in blood pressure. 23 Even more moderate increases over a longer period are associated with chronic diseases, 24 all of which are exacerbated when weight is gained during adolescence and early adulthood to have later life repercussions. 25 26 The interruption of individual routines and confinement may lead to a calorie imbalance pushed by concomitant lower physical activity and increased sedentary time, as well as irregular eating patterns and frequent snacking.…”
Section: Discussionmentioning
confidence: 99%
“…With LCGMM, individual model-predicted BMI values and slopes could be used to characterise the critical period to develop hypertension. 27 On the basis of lifecourse epidemiology theory, exposure at a specific life period can greatly affect the development of diseases in later life. 37 As a result, our study suggested that maintaining a high BMI value or a rapid increase in BMI may increase the risk of hypertension in later life.…”
Section: Discussionmentioning
confidence: 99%